Optimizing CROP GEOMETRY IN Kufri Chipsona-3 and Kufri Himsona for higher grade tuber yield and quality - Kumar, Parveen; Singh, B P; Kumar, Rajeev; Sandhu, K S; Kumar, Dinesh; Pandey, S K; Singh, S V (Potato Journal, 2015)
A field study was conducted at Central Potato Research Institute Campus, Modipuram, India during 2008- 2010 with two processing varieties Kufri Himsona and Kufri Chipsona-3 in main plot and five crop geometry treatments (67.5 √× 20, 67.5 √× 22.5, 67.5 √× 25, 67.5 ×√ 27.5 and 67.5 √× 30 cm). Growth traits, processing grade tuber number and yield and processing quality parameters were not influenced by crop geometry. Tuber number/plant, percent processing grade tuber and average processing grade tuber weight steadily increased with increased intra-row spacing from 22 to 30 cm. Net returns (Rupess 126,000/ha) and B:C ratio (2.69) was highest at 67.5 ×√ 30 cm crop geometry. Processing grade tuber number and yield, net returns, B:C ratio was higher for cv. Kufri Chipsona-3 than Kufri Himsona. Tuber number/plant, tuber dry matter and chip yield was higher and oil per cent in chips were lower in cv. Kufri Himsona compared to Kufri Chipsona-3. Tuber dry matter yield, chip colour score and glucose content were statistically similar in both the cultivars. Study suggests that cvs Kufri Chipsona-3 and Kufri Himsona may be raised at 67.5 √× 30 cm crop geometry for higher tuber yield, net returns and better processing quality.